Features of alcohol harm reduction advertisements that most motivate reduced drinking among adults: An advertisement response study - Wakefield, M.; Brennan, E.; Dunstone, K.; Durkin, S.; Dixon, H.; Pettigrew, Simone; Slater, M. (BM J Group, 2017)
Objectives To improve the effectiveness of alcohol harm reduction mass media campaigns, this study aimed to (1) identify existing advertisements (ads) with greatest potential to motivate reduced alcohol consumption, (2) assess consistency across audience subgroups in ad effectiveness and (3) identify ad features associated wi th effectiveness. Design Cross-sectional online ad response study with random assignment to view ads. Participants 2174 Australian adult weekly drinkers recruited from an online panel. Procedure Participants were randomly assigned to view three of 83 English-language alcohol harm reduction ads. Each ad was viewed and rated by a mean of 79 participants. Outcome measure After viewing each ad, participants reported the extent to which they felt motivated to reduce their drinking. Ads were ranked from most to least motivating using predicted means adjusted for demographic characteristics and alcohol consumption. We compared the characteristics of the top-ranked 15% of ads (most motivating) with the middle 70% and bottom 15%. Results An ad about the link between alcohol and cancer ('Spread') was most motivating, whereas an ad that encouraged drinking water instead of beer ('Add nothing') was least motivating. Top-ranked ads were more likely than other ads to feature a 'why change' message and less likely to carry a 'how to change' message; more likely to address long-term harms; more likely to be aimed at the general adult drinking population and more likely to include drinking guidelines. There was substantial overlap in top-ranked ads for younger versus older adults, men versus women and high-risk versus low-risk drinker subgroups. Conclusions The effectiveness of alcohol harm reduction campaigns may be improved by directly communicating alcohol's long-term harms to the general adult population of drinkers along with drinking guidelines. By doing so, campaigns can also efficiently influence high-risk drinkers and key demographic subgroups.